2012
DOI: 10.1084/jem.20110216
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 induces Ikaros splicing to promote immunoglobulin gene recombination

Abstract: During murine B cell development, PI3 kinase inhibits Ig gene rearrangement by suppressing FoxO1, which mediates Ikaros mRNA splicing; Ikaros is needed for Ig gene recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 54 publications
2
59
0
Order By: Relevance
“…It is tempting to speculate that signaling pathways modulated by miR-17 and miR-19b may cross-talk with each other. Intriguingly, it has been shown that, in pro-B cells, the activation of PI3K is essential in controlling IKZF1 expression and therefore successful VDJ recombination (46). However, under both T H 1 and T H 17 conditions, manipulation of miR-17 did not cause any measurable impact on PTEN expression (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…It is tempting to speculate that signaling pathways modulated by miR-17 and miR-19b may cross-talk with each other. Intriguingly, it has been shown that, in pro-B cells, the activation of PI3K is essential in controlling IKZF1 expression and therefore successful VDJ recombination (46). However, under both T H 1 and T H 17 conditions, manipulation of miR-17 did not cause any measurable impact on PTEN expression (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…10,12 The immunoglobulin joining chain is involved in immunoglobulin maturation, [31][32][33] whereas IKAROS controls the processing of immature B-cell receptors into immunoglobulins. 34,35 Whether IKZF1 deletions functionally affect this maturation process clearly warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…4 G and H), indicating that Ras inhibits receptor editing via the PI3K pathway. During B-cell development, PI3K has been shown to down-modulate rag transcription by reducing the protein levels of FoxO1, a transcription factor necessary for Rag expression (18,47). Studies in splenic B cells suggest that PI3K signaling impinges on both mRNA and protein levels of FoxO1 (48).…”
Section: Ras Usesmentioning
confidence: 99%